If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + -1i)(x + -1i)(x + -1i) + (x + i)(x + i)(x + i) = 0 Reorder the terms: (-1i + x)(x + -1i)(x + -1i) + (x + i)(x + i)(x + i) = 0 Reorder the terms: (-1i + x)(-1i + x)(x + -1i) + (x + i)(x + i)(x + i) = 0 Reorder the terms: (-1i + x)(-1i + x)(-1i + x) + (x + i)(x + i)(x + i) = 0 Multiply (-1i + x) * (-1i + x) (-1i * (-1i + x) + x(-1i + x))(-1i + x) + (x + i)(x + i)(x + i) = 0 ((-1i * -1i + x * -1i) + x(-1i + x))(-1i + x) + (x + i)(x + i)(x + i) = 0 Reorder the terms: ((-1ix + 1i2) + x(-1i + x))(-1i + x) + (x + i)(x + i)(x + i) = 0 ((-1ix + 1i2) + x(-1i + x))(-1i + x) + (x + i)(x + i)(x + i) = 0 (-1ix + 1i2 + (-1i * x + x * x))(-1i + x) + (x + i)(x + i)(x + i) = 0 (-1ix + 1i2 + (-1ix + x2))(-1i + x) + (x + i)(x + i)(x + i) = 0 Reorder the terms: (-1ix + -1ix + 1i2 + x2)(-1i + x) + (x + i)(x + i)(x + i) = 0 Combine like terms: -1ix + -1ix = -2ix (-2ix + 1i2 + x2)(-1i + x) + (x + i)(x + i)(x + i) = 0 Multiply (-2ix + 1i2 + x2) * (-1i + x) (-2ix * (-1i + x) + 1i2 * (-1i + x) + x2(-1i + x)) + (x + i)(x + i)(x + i) = 0 ((-1i * -2ix + x * -2ix) + 1i2 * (-1i + x) + x2(-1i + x)) + (x + i)(x + i)(x + i) = 0 Reorder the terms: ((-2ix2 + 2i2x) + 1i2 * (-1i + x) + x2(-1i + x)) + (x + i)(x + i)(x + i) = 0 ((-2ix2 + 2i2x) + 1i2 * (-1i + x) + x2(-1i + x)) + (x + i)(x + i)(x + i) = 0 (-2ix2 + 2i2x + (-1i * 1i2 + x * 1i2) + x2(-1i + x)) + (x + i)(x + i)(x + i) = 0 Reorder the terms: (-2ix2 + 2i2x + (1i2x + -1i3) + x2(-1i + x)) + (x + i)(x + i)(x + i) = 0 (-2ix2 + 2i2x + (1i2x + -1i3) + x2(-1i + x)) + (x + i)(x + i)(x + i) = 0 (-2ix2 + 2i2x + 1i2x + -1i3 + (-1i * x2 + x * x2)) + (x + i)(x + i)(x + i) = 0 (-2ix2 + 2i2x + 1i2x + -1i3 + (-1ix2 + x3)) + (x + i)(x + i)(x + i) = 0 Reorder the terms: (-2ix2 + -1ix2 + 2i2x + 1i2x + -1i3 + x3) + (x + i)(x + i)(x + i) = 0 Combine like terms: -2ix2 + -1ix2 = -3ix2 (-3ix2 + 2i2x + 1i2x + -1i3 + x3) + (x + i)(x + i)(x + i) = 0 Combine like terms: 2i2x + 1i2x = 3i2x (-3ix2 + 3i2x + -1i3 + x3) + (x + i)(x + i)(x + i) = 0 Reorder the terms: -3ix2 + 3i2x + -1i3 + x3 + (i + x)(x + i)(x + i) = 0 Reorder the terms: -3ix2 + 3i2x + -1i3 + x3 + (i + x)(i + x)(x + i) = 0 Reorder the terms: -3ix2 + 3i2x + -1i3 + x3 + (i + x)(i + x)(i + x) = 0 Multiply (i + x) * (i + x) -3ix2 + 3i2x + -1i3 + x3 + (i(i + x) + x(i + x))(i + x) = 0 -3ix2 + 3i2x + -1i3 + x3 + ((i * i + x * i) + x(i + x))(i + x) = 0 Reorder the terms: -3ix2 + 3i2x + -1i3 + x3 + ((ix + i2) + x(i + x))(i + x) = 0 -3ix2 + 3i2x + -1i3 + x3 + ((ix + i2) + x(i + x))(i + x) = 0 -3ix2 + 3i2x + -1i3 + x3 + (ix + i2 + (i * x + x * x))(i + x) = 0 -3ix2 + 3i2x + -1i3 + x3 + (ix + i2 + (ix + x2))(i + x) = 0 Reorder the terms: -3ix2 + 3i2x + -1i3 + x3 + (ix + ix + i2 + x2)(i + x) = 0 Combine like terms: ix + ix = 2ix -3ix2 + 3i2x + -1i3 + x3 + (2ix + i2 + x2)(i + x) = 0 Multiply (2ix + i2 + x2) * (i + x) -3ix2 + 3i2x + -1i3 + x3 + (2ix * (i + x) + i2(i + x) + x2(i + x)) = 0 -3ix2 + 3i2x + -1i3 + x3 + ((i * 2ix + x * 2ix) + i2(i + x) + x2(i + x)) = 0 Reorder the terms: -3ix2 + 3i2x + -1i3 + x3 + ((2ix2 + 2i2x) + i2(i + x) + x2(i + x)) = 0 -3ix2 + 3i2x + -1i3 + x3 + ((2ix2 + 2i2x) + i2(i + x) + x2(i + x)) = 0 -3ix2 + 3i2x + -1i3 + x3 + (2ix2 + 2i2x + (i * i2 + x * i2) + x2(i + x)) = 0 Reorder the terms: -3ix2 + 3i2x + -1i3 + x3 + (2ix2 + 2i2x + (i2x + i3) + x2(i + x)) = 0 -3ix2 + 3i2x + -1i3 + x3 + (2ix2 + 2i2x + (i2x + i3) + x2(i + x)) = 0 -3ix2 + 3i2x + -1i3 + x3 + (2ix2 + 2i2x + i2x + i3 + (i * x2 + x * x2)) = 0 -3ix2 + 3i2x + -1i3 + x3 + (2ix2 + 2i2x + i2x + i3 + (ix2 + x3)) = 0 Reorder the terms: -3ix2 + 3i2x + -1i3 + x3 + (2ix2 + ix2 + 2i2x + i2x + i3 + x3) = 0 Combine like terms: 2ix2 + ix2 = 3ix2 -3ix2 + 3i2x + -1i3 + x3 + (3ix2 + 2i2x + i2x + i3 + x3) = 0 Combine like terms: 2i2x + i2x = 3i2x -3ix2 + 3i2x + -1i3 + x3 + (3ix2 + 3i2x + i3 + x3) = 0 Reorder the terms: -3ix2 + 3ix2 + 3i2x + 3i2x + -1i3 + i3 + x3 + x3 = 0 Combine like terms: -3ix2 + 3ix2 = 0 0 + 3i2x + 3i2x + -1i3 + i3 + x3 + x3 = 0 3i2x + 3i2x + -1i3 + i3 + x3 + x3 = 0 Combine like terms: 3i2x + 3i2x = 6i2x 6i2x + -1i3 + i3 + x3 + x3 = 0 Combine like terms: -1i3 + i3 = 0 6i2x + 0 + x3 + x3 = 0 6i2x + x3 + x3 = 0 Combine like terms: x3 + x3 = 2x3 6i2x + 2x3 = 0 Solving 6i2x + 2x3 = 0 Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-2x3' to each side of the equation. 6i2x + 2x3 + -2x3 = 0 + -2x3 Combine like terms: 2x3 + -2x3 = 0 6i2x + 0 = 0 + -2x3 6i2x = 0 + -2x3 Remove the zero: 6i2x = -2x3 Divide each side by '6x'. i2 = -0.3333333333x2 Simplifying i2 = -0.3333333333x2 Combine like terms: -0.3333333333x2 + 0.3333333333x2 = 0.0000000000 i2 + 0.3333333333x2 = 0.0000000000 The solution to this equation could not be determined.
| 11+a=11+8a | | 8sinx=2sinx | | 4(2x+1)=-1 | | 36-2x=24 | | 115=15-25x | | 115=-25x | | 3x+12+4x-1=180 | | 6u^2+8u+25=0 | | 1y+5=2x+2 | | 19a+19b+4c+4c-2b-4a=0 | | X+(X*.08)=39.13 | | 6u^2+7u+25=0 | | 10-y=12y+7y | | 14+3x=52 | | 7x-9y=-8 | | (x-i)+(x+i)=0 | | e^(-6)=(1)/(e^(6)) | | 7x-4=53 | | V+12=-11 | | X+(X*.1)=40.76 | | 3c-11=4 | | 15f=1.20 | | v^2+9=-14 | | 8.11/10 | | 21+4x=41 | | 366=6m | | 18p+17q+p-3q-4p=0 | | 11+11a=-11-11a | | 6v^2-12v-14=-8 | | 19-2p=15 | | 6(3y+8)= | | 4a-b+4b-a=180 |